Inhalation of Carbon Monoxide Protects Liver Against Warm Ischemia-Reperfusion Injury in CLAWN Miniature Swine. (July 2018) - Murokawa, Takahiro; Sahara, Hisashi; Sekijima, Mitsuhiro; Iwanaga, Takehiro; Ariyoshi, Yuichi; Ichinari, Yurika; Shimizu, Akira; Yamada, Kazuhiko
Abstract : Background: Carbon monoxide (CO) is produced endogenously as a by-product of heme catalysis, and has been shown to reduce hepatic ischemia-reperfusion injury (IRI) in murine models. We previously reported the beneficial effects of perioperative low-dose inhalation of CO on lung IRI in CLAWN miniature swine. Since CO is well known to be a toxic gas, translational research to evaluate the safety and effectiveness of CO-therapy in various organs using large animals is essential prior to its use in the clinic. The aims of this research were to establish a large animal model of hepatic warm IRI and to evaluate the cytoprotective effects of inhaled CO on ameliorating IRI in this model. Methods: Hepatic warm ischemia was induced for 45 minutes by clamping portal vein and proper hepatic artery under the extracorporeal portojugular bypass to prevent visceral congestion. Six CLAWN miniature swine were divided evenly into 2 groups: a CO-treated group and a control group. In the CO-treated group, animals were continuously inhaled with CO from the time of laparotomy until 2 hours after reperfusion (345 minutes in total). CO concentration was adjusted based on COHb levels in the blood (⩽15%). Liver injury was evaluated by serum AST/ALT levels as well as histologies of liver biopsies. Serum cytokine levels (TNF-α, IL-6, HMGB1) were measured to characterize the inflammatory response to hepatic IRI and evaluate the effect of CO on that response. Results: Serum AST/ALT levels were markedly increased following 45-minutes hepatic warm ischemia and recovering by day 4. Peak AST/ALT levels of the CO-treated group were significantly lower than those of the control group (control vs CO-treated; AST: 2224 ± 326 vs 456 ± 81 U/L; ALT: 98 ± 50 vs 23 ± 5 U/L; p <0.05). Liver biopsies at 2 hours after reperfusion from the control animals demonstrated hemorrhage, necrosis, congestion and extensive vacuolization of the hepatocytes associated with neutrophil infiltrates. TUNEL staining revealed diffuse apoptotic cells among hepatocytes as well. In sharp contrast, biopsies at 2 hours showed limited areas of congestion and vacuolization or apoptotic cells of the hepatocytes in the CO-treated group. Liver biopsies at 4 days after reperfusion in the control group demonstrated numerous positive PCNA cells indicating active liver regeneration following IRI, while minimal positive PCNA cells in the CO-treated group. Furthermore, CO-therapy successfully inhibited to increase in serum levels of proinflammatory cytokines especially for HMGB1 (control vs CO-treated: 163 ± 56 vs 21 ± 7 ng/mL; 1-hour reperfusion; p <0.05, 164 ± 43 vs 14 ± 2 ng/mL; 2-hour reperfusion; p <0.05). Conclusion: To our knowledge, this is the first demonstration that the perioperative administration of low-dose inhaled CO decreases warm IRI in livers in a clinically relevant, large animal model. This protective effect is mediated in part by inhibiting proinflammatory responses and apoptosis of the hepatocytes.